(untitled) (Fiep Bulletin - online, 2016)
The practice of physical activity reduces the risk of health problems in the short and long term. Among the practices, cycling is on the rise. The present study aimed to evaluate the body composition of athletes in the cycling group "Pedal Noturno" from Teresina- PI. This is a quantitative and descriptive study. It was assessed 30 adult participants aged 18-60 years, where this sample was chosen intentionally. There was a measurement of weight and height and then it was calculated the body mass index (BMI), in addition, a questionnaire for investigation of health perception, reason and perceived benefits of the practice was applied. It was obtained as a result a large number of cyclists inserted in the classification of BMI acceptable / ideal, as health perceptions, the majority considered themselves in a good condition and with regard to the benefits provided by cycling, weight reduction is the most cited in the literature of aerobic activities which provide this action but also improves the cardiorespiratory system and the quality of life of these individuals. It can be concluded by the end of the study that the cyclism group "Pedal Noturno" is a heterogeneous group, with ideal body composition, showing a good awareness of health status.